Assessment of Heavy Metals Safety in Barbecued Meat Samples Sold in Wudil, Kano State, Nigeria - Sabiu Wada Haruna; Ruslan Shamsuddeen; Ansar Bilyaminu Adam; Musa Yahaya Abubakar (Department of Chemistry, Universitas Negeri Malang, 2025)
This study evaluated the concentrations of Cadmium (Cd), Chromium (Cr), Lead (Pb), and Zinc (Zn) in barbecued meat samples sold in Wudil, comparing the results with World Health Organization (WHO) and Food and Agriculture Organization (FAO) safety standards. Eight samples (A-H) were analyzed using standard laboratory procedures, and the concentrations of these metals were measured in parts per million (ppm). The mean concentrations of Cd ranged from 0.43 to 0.78 ppm, with all samples exceeding the WHO permissible limit of 1.00 µg/g. For Cr, levels varied between 10.84 and 25.84 ppm, surpassing the WHO/FAO guideline of 1.00 µg/g, raising concerns about potential health risks from prolonged exposure. Lead concentrations were notably below the maximum allowable limit of 6.00 µg/g, ranging from 0.00 to 5.22 ppm. Zinc, an essential trace element, was present in all samples at concentrations between 14.09 and 31.21 ppm, within the permissible limits of 50.00 µg/g. Overall, the findings reveal varying levels of heavy metal contamination in barbecued meat samples sold in Wudil, with Chromium and Cadmium levels posing a potential risk to public health. Continuous monitoring and regulatory interventions are recommended to ensure the safety of consumers of these meat products.References Abubakar, M. Y., Haladu, M., Titilayo, O. A., & Adam, A. B. (2024). Effect and Remediation of Environmental Pollution on the Concept of Chemistry Review. African Journal of Sciences and Traditional Medicine, 1(1),440449. Adam, A. B., Abubakar, M. Y., Aneshi, A., Abdullahi, S., Ataitiya, H., & Garba, F. (2024). Comparative Studies and Proximate Analysis of Brown Beans as a Plant-Based Meat Alternative. International Research Journal of Chemistry, 43, 38-45. Adegbola, R. (2013). Heavy metal contamination in street-vended barbecued meat. Journal of Environmental Science, 23(4), 201-215. Ahmad, K. B., Adam, A. B., Bilkisu, I. A., Umar, F. S., & Kahtan, A. H. (2024). Assessment of Heavy Metals in Human Scalp Hair. Tropical Journal of Engineering, Science and Technology, 3(1), 1-7. Baykov, B., Stoyanov, M., & Gugova, M. (1996). Cadmium and lead bioaccumulation in male goats fed with contaminated forage. Journal of Animal Science, 74(5), 1537-1543. Demirezen, D., & Uruc, K. (2006). Comparative study of trace elements in certain fish, meat, and meat products. Food Chemistry, 104(3), 1075-1080. Goyer, R. A. (1997). Toxic and essential metal interactions. Annual Review of Nutrition, 17(1), 37-50. Miranda, M., Lopez-Alonso, M., Castillo, C., & Hernandez, J. (2005). Impact of environmental pollution on metal content in animal products. Journal of Veterinary Research, 36(3), 281-287. Oluwasanmi, A. I., Adam, A. B., & Abubakar, M. Y. (2024). Comprehensive Review On Heavy Metal Contamination In Air From Metal Processing Industries: Sources, Dispersion, And Mitigation Strategies. Bİlsel International Gordİon Scientific Research Congress 19-20 September 2024- Ankara/ Türkİye. Sahrawat, K. L., Burford, J. R., & Diatta, S. (2002). Digestion method for determining trace metal concentrations in soil. Communications in Soil Science and Plant Analysis, 33(5-6), 735-740. Santhi, D., Balakrishnan, V., Kalaikannan, A., & Radhakrishnan, K. (2008). Presence of heavy metals in pork products in Chennai (India). American Journal of Food Technology, 3(3), 192-199. SCAN (Scientific Committee on Animal Nutrition). (2003). Opinion of the scientific committee on animal nutrition on the dioxin contamination of animal feed. European Journal of Animal Science, 42(1), 45-57. Yusuf, K. A., Adegbola, R. A., & Ajibola, T. B. (2002). Determination of heavy metal residues in cattle reared near industrial areas. Nigerian Journal of Animal Production, 27(3), 211-217.